DEVELOPMENT OF SEISMIC MAPS AND SITE-SPECIFIC ANALYSIS FOR OFFSHORE STRUCTURES, CASE STUDY NORTH COAST OF JAVA USING ISO 19901-2:2004 - Damara Aditramulyadi, Dega
Indonesia currently does not have a specific standard in designing earthquakeresistant structures for offshore structures. In 2004, the International Organization for Standardization (ISO) issued ISO 19901-2:2004 which provides guidance on methods that are more traceable in determining earthquake loads than the standards commonly used today. In this standard, seismic analysis is carried out for two earthquake levels: Extreme Level Earthquake (ELE) and Abnormal Level Earthquake (ALE). This study presents the development of seismic hazard maps for a 1000-year return period on the north coast of Java Island, Indonesia, and design spectra for a case study of L3 structures at the study site. The development of seismic maps is carried out using the Probabilistic Seismic Hazard Analysis (PSHA) method by USGS PSHA program. The method for determining earthquake acceleration for structural design provided by ISO 19901- 2:2004 consists of two methods, namely the simplified method and the detailed (sitespecific) method. In this study, both methods were used to obtain the magnitude of the earthquake acceleration required for the design of the foundation of the offshore structure, both shallow and deep foundations. Seismic zones based on ISO 19901-2:2004 on the north coast of Java within the scope of this study majority fall into category 2, with a small portion of considerable distance fall into category 1. For both ALE and ELE earthquake events of the L3 structure with 2.5s natural period at the study site, the acceleration value for shallow foundations will be greater when the simplified ISO 19901-2:2004 method is used. Meanwhile, the site-specific method provides a slightly more conservative value for the deep foundations.